Wooden Toys or the Tree Palimpsest: Mythopoetic Vessels in Ancient Mediterranean Cultures - Vaz-Romero Trueba, Oriol (Eikón / Imago, 2022)
A palimpsest defines a superposition of events, like a piece that has been redrafted. Wooden toys take shape from the flesh of tree, giving it a second "life", not natural but symbolic. Digging through archaeological materials, iconographic and literary sources, we will explore how the craftsman, anonymous maker often overlooked by art historians, turns wood into an image, that is to say a semiotic artifact serving the most diverse children and adults imaginaries. Likewise, we will endeavour to link the history of these toys with some technical advances, such as the discovery of the pedal lathe in the 12th century and the introduction of hydraulic mechanisms in the 16th century, which has liberated the maker’s hands and fine-tuned the finishing of the pieces. Already present in the infant tombs of Coptic Egypt, 3rd and 4th centuries AC, this “minimal sculpture” was introduced into the daily life of the main Mediterranean and continental cultures, surviving even the current Global Plastic Village. Furthermore, yo-yos, tops, windmill toys and hobbyhorses, dolls and rocking toys lead us along the paths of traditional animisms and the Christian literature, both holders of folk tales.
Keywords: Toy; Wood; Tree; Mythopoiesis; History of Mentalities; Mediterranean Cultures